2001
DOI: 10.3109/2000-1967-144
|View full text |Cite
|
Sign up to set email alerts
|

Aphasia in Multiple Sclerosis

Abstract: Aphasia has rarely been reported in multiple sclerosis (MS). In this article a case with MS presenting as purely global aphasia during an exacerbation of MS is reported with clinical and MRI (magnetic resonance imaging) findings. MRI demonstrated giant plaques mimicking a cerebral tumour with surroundings characterised by oedematous transformations in the left frontal and parietal lobes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Our study describes the largest cohort to date and found a prevalence of 0.81%, suggesting that this symptom is not as rare in MS as previously thought. Acute aphasia occurring during a relapse of the disease has to be distinguished from chronic language disorders in MS.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Our study describes the largest cohort to date and found a prevalence of 0.81%, suggesting that this symptom is not as rare in MS as previously thought. Acute aphasia occurring during a relapse of the disease has to be distinguished from chronic language disorders in MS.…”
Section: Discussionsupporting
confidence: 54%
“…The second is acute aphasia and has rarely been described in MS: Estimates of its frequency based on several studies range from 0.7 to 3%, but to our knowledge, only 16 case reports have been published in the literature since 1977. [1][2][3][4][5][6][7] Among these patients, two experienced acute aphasia as the first clinical manifestation of the disease, five presented aphasic status epilepticus documented by EEG, and eight had MRI findings with giant plaques. Our aim was to study the clinical and radiologic characteristics of a multicentric cohort of 22 MS patients with acute aphasia.…”
mentioning
confidence: 99%